Influences on understanding of a verbally presented police caution amongst adults involved in the criminal justice system: a systematic review. Issue 1 (2nd January 2021) - Rendall, Michael; MacMahon, Ken
Abstract : This review systematically examines the literature exploring comprehension of a verbally presented police caution and the suggested factors influencing this, amongst adults within the criminal justice system. An electronic literature search returned 438 titles, with screening leaving 13 articles considered appropriate for the review question. The majority of these were USA studies, with two UK and two Canadian studies. Heterogeneous study methodologies permit only a narrative approach to pooling the data. Findings indicate that a considerable proportion of this population have difficulty fully understanding the caution. Higher IQs and verbal comprehension are positively associated with performance. The studies also indicate that some factors that may appear intuitively related to comprehension, such as prior caution exposure, education, age and mental health, may not be linked to performance. The literature generally used broad inclusion criteria, which increased potential for confounders and reduced opportunity to draw out probable predictors.